A van der Waals ferroelectric switchable diode with ultra-high nonlinearity factor - Ruibin Duan; Jiahao Yan; Dehuan Meng; Yuehui Wang; Dengqin Xu; Minghe Zhang; Dunshan YU; Tang, Kechao; Dong, Junchen; Han, Dedong; Xing Zhang (Applied Surface Science, 2025)
Two-dimensional (2D) van der Waals ferroelectric materials have emerged as promising candidates for miniaturized devices due to their atomically thin structures and unique ability to maintain ferroelectricity even at reduced dimensions. Recent research indicates that the interfacial barriers between semiconductors and ferroelectrics can be modulated by polarization charges, with ferroelectric polarization—reversible by an external electric field—playing a crucial role in the switchable diode effect. In this work, we investigate a room-temperature switchable ferroelectric diode (Fe-diode) based on a MoS2/α-In2Se3 heterojunction. The out-of-plane ferroelectric properties of the α-In2Se3 layer enable efficient modulation of the Schottky barriers at the MoS2/α-In2Se3 interface through external voltage application, thereby achieving a notable switchable diode effect with a nonlinearity of up to 934. By exploiting the inherent nonlinearity, the ferroelectric diode can effectively generate complex signal waveforms, making it highly suitable for secure communication systems. These findings make the ferroelectric diode a potential candidate for enhancing confidentiality in future communication technologies, protecting data against eavesdropping and unauthorized access.
Keywords: Ferroelectric diode; nonlinearity; polarization; α-InSe